Act No. 6 of 2023 Effect on Management Authority of Coastal Areas and Small Islands - Ade Gunawan; Amiek Soemarmi (Universitas Islam Sultan Agung, 2023)
The presence of the state in people's lives today can be found in various sectors of life in society. The emergence of the notion of the welfare state requires that the state intervene in efforts to realize the welfare of its people. One of the fields in which the state is present in efforts to realize the welfare of its people is the management of Coastal Zone and Small Islands. The utilization and management of water resources in the Coastal Zone and Small Islands have undergone developments in line with changes in the legal framework. This research which uses normative juridical research methods with a statutory approach, discusses the development of regulations regarding the basis for the management and utilization of water resources in the Coastal Zone and Small Islands. The results of the study show that the differences in the basic forms of utilization and management of water resources in the Coastal Zone and Small Islands from what was originally in the form of rights to permits and changed back to business permits and the differences in parties having the authority to grant these rights have significant implications.